2012
DOI: 10.1159/000343921
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Signal Peptides on the Secretion of β-Cyclodextrin Glucanotransferase in <b><i>Lactococcus lactis</i></b> NZ9000

Abstract: Cyclodextrin glucanotransferase (CGTase) is an extracellular enzyme which catalyzes the formation of cyclodextrin from starch. The production of CGTase using lactic acid bacterium is an attractive alternative and safer strategy to produce CGTase. In this study, we report the construction of genetically modified Lactococcus lactis strains harboring plasmids that secrete the Bacillus sp. G1 β-CGTase, with the aid of the signal peptides (SPs) SPK1, USP45 and native SP (NSP). Three constructed vectors, pNZ:NSP:CGT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 70 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…More recently, we have isolated a novel signal peptide, SPK1 from Pediococcus pentasaceus , with the ability to secrete heterologous proteins with efficiencies comparable to Usp45 in L. lactis [25]. When SPK1 was used to secrete β-cyclodextrin glucanotransferase, although secretion efficiency was higher than USP45, total yield was found to be lower [26], thus demonstrating the complex effects brought upon by SPs, not only on the secretion of heterologous proteins, but on total protein yield as well.…”
Section: The Lactococcal Molecular Toolboxmentioning
confidence: 99%
“…More recently, we have isolated a novel signal peptide, SPK1 from Pediococcus pentasaceus , with the ability to secrete heterologous proteins with efficiencies comparable to Usp45 in L. lactis [25]. When SPK1 was used to secrete β-cyclodextrin glucanotransferase, although secretion efficiency was higher than USP45, total yield was found to be lower [26], thus demonstrating the complex effects brought upon by SPs, not only on the secretion of heterologous proteins, but on total protein yield as well.…”
Section: The Lactococcal Molecular Toolboxmentioning
confidence: 99%
“…Cano‐Garrido et al () reported the solubility of aggregation‐prone GFP variant (VP1GFP), expressed using pNZ8148 in L. lactis , was influenced by time, culture conditions and growth temperature, which have a dramatic effect not only on protein yield but also on protein solubility and conformational quality that were particularly favoured under fermentative anaerobic metabolism. Despite testing an extended duration of expression (6–12 h) at different growth temperatures (including the optimum 30°C), as previously reported for secretion of recombinant proteins containing USP45 (Subramaniam et al ; Siaw et al ), the expressed recombinant S‐Ara2.02‐H remained insoluble and intracellular even after 24 h of expression. Subsequent purification and refolding of the insoluble rS‐Ara2.02‐H recombinant protein produced in L. lactis was performed to verify its identity and allergenicity prior to prophylactic study.…”
Section: Discussionmentioning
confidence: 82%
“…[1] Bacterial culture in the form of glycerol stock, maintained at ¡20 C, was used for inoculum preparation. For this purpose, the stock culture was thawed and streaked on M17 agar (Merck, Germany) plate followed by incubation at 30 C for 24 h. A single colony was inoculated in 10 mL of M17 broth and incubated overnight followed by a sub-culture in fresh M17 broth and incubation at the same conditions.…”
Section: Strain and Inoculum Preparationmentioning
confidence: 99%
“…The expression system used in the present study is the nisin-controlled expression (NICE) system [1,40]. Mierau et al [40] conducted a study in order to optimize the L. lactis NICE system for industrial applications.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation